AKUNTABILITAS DAN TRANSPARANSI KEUANGAN DESA: SINTESIS TEMATIK LITERATUR - Halid, Fityan; Amaliah, Tri Handayani; Mahdalena (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Village financial management requires transparent and accountable governance practices as villages play an increasingly significant role in managing public funds. Although numerous studies have examined this issue, existing findings remain fragmented and partial. This study aims to systematically synthesize research findings related to accountability and transparency in village financial management. A Systematic Literature Review approach was employed by searching journal articles indexed in Google Scholar and published between 2021 and 2025, resulting in 25 articles that met the inclusion criteria. Data were analyzed using a thematic analysis approach supported by ATLAS.ti software. The synthesis results indicate that transparency and accountability are central issues in village financial management; however, in practice, they are still often understood and implemented in an administrative and formalistic manner. The quality of village financial governance is shaped by the interaction between the use of technology, particularly village financial information systems, the capacity of village government personnel, and the effectiveness of supervision and community participation mechanisms. The findings also reveal that limited personnel capacity, weak supervision, and low levels of community participation constitute major obstacles to achieving substantive accountability. This study underscores that improving transparency and accountability in village financial management requires a systemic and integrated approach that goes beyond administrative or technological aspects alone and emphasizes the strengthening of institutional capacity and public participation